2019
DOI: 10.1242/dev.163618
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous and redundant roles of Hey1 and HeyL in muscle stem cells: HeyL requires Hes1 to bind diverse DNA sites

Abstract: The undifferentiated state of muscle stem (satellite) cells (MuSCs) is maintained by the canonical Notch pathway. Although three bHLH transcriptional factors, Hey1, HeyL and Hes1, are considered to be potential effectors of the Notch pathway exerting anti-myogenic effects, neither HeyL nor Hes1 inhibits myogenic differentiation of myogenic cell lines. Furthermore, whether these factors work redundantly or cooperatively is unknown. Here, we showed cellautonomous functions of Hey1 and HeyL in MuSCs using conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 52 publications
(80 reference statements)
5
39
0
Order By: Relevance
“…We found that MyoD and MyoG are crucial TFs for myogenic differentiation, especially through regulation of Mef2c and Heyl (Figure 4D), which were also previously shown to provide key contributions to myogenic differentiation 36‐38 . We thus developed a correlation network between these four TFs and 149 of their correlated DE lncRNAs to improve our understanding of the function of lncRNAs (Figure 4E, Figure ).…”
Section: Resultssupporting
confidence: 55%
“…We found that MyoD and MyoG are crucial TFs for myogenic differentiation, especially through regulation of Mef2c and Heyl (Figure 4D), which were also previously shown to provide key contributions to myogenic differentiation 36‐38 . We thus developed a correlation network between these four TFs and 149 of their correlated DE lncRNAs to improve our understanding of the function of lncRNAs (Figure 4E, Figure ).…”
Section: Resultssupporting
confidence: 55%
“…The Pax7 CreERT2(Fan)/+ regeneration phenotype is consistent with previous findings (Mademtzoglou et al, 2018) and likely related to expression of only one Pax7 allele after CreERT2 insertion (Lepper et al, 2009). Leaky Cre recombinase activation and downregulation of Hey1, which is required to maintain satellite cells, in Pax7 CreERT2(Fan)/+ mice not treated with tamoxifen (Noguchi et al, 2019) could affect satellite cells during muscle regeneration.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, we hypothesized that canonical Notch signaling is responsible for MyoD suppression in proliferating MuSCs in overloaded muscle. Hey1 , Heyl, and Hes1 are crucial primary targets of canonical Notch signaling in MuSCs (Fukada et al, 2011; Lahmann et al, 2019) and function to suppress myogenic differentiation as Hey–Hes1 heterodimer complexes (Noguchi et al, 2019). Moreover, Hey1 and Heyl are both expressed in quiescent MuSCs, although their expression is drastically reduced during injury induced MuSC activation (Figure 3—figure supplement 1) (Fukada et al, 2011; Mourikis et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lahmann et al indicated that Hes1 controls oscillatory Myod expression in activated/proliferating MuSCs (Lahmann et al, 2019). We previously reported that neither Hey1 (Hey1-KO) nor Heyl single-knockout (HeyL-KO) mice show abnormalities in regenerative ability, MyoD and myogenin expression, or MuSC number; however, double-KO mice exhibit severe regenerative defects due to a reduction in MuSC number resulting from increased MyoD and myogenin expression in the MuSCs (Fukada et al, 2011; Noguchi et al, 2019). When MuSCs respond to muscle injury, Hey1 and Heyl expression levels are drastically decreased; therefore, activation/proliferation of MuSCs in injured muscle do not require Hey1 and Heyl expression.…”
Section: Introductionmentioning
confidence: 99%